Gut Microbiomes of Endangered Przewalski’s Horse Populations in Short- and Long-Term Captivity: Implication for Species Reintroduction Based on the Soft-Release Strategy - Tang, Liping; Li, Yimeng; Srivathsan, Amrita; Gao, Yunyun; Li, Kai; Hu, Defu; Zhang, Dong (Frontiers in Microbiology, 2020)
Captivity maybe the only choice for survival of many endangered vertebrates, and understanding its broad effects is important for animal management and conservation, including breeding endangered species for subsequent release. Extreme environmental changes during captivity may influence survival ability in the wild. Captivity decreases gut bacterial diversity in a wide range of animals. However, most studies directly compare animals living in captivity with those in the wild, and there is a lack of understanding of effects of gradient shift in lifestyle during species reintroduction based on the soft-release strategy, which involves a confinement period in a field enclosure. Here, we used 16S rRNA amplicon sequencing to analyze gut microbiomes of 11 captive and 12 semi-wild Przewalski’s horses (PH; Equus ferus przewalskii) under the same captivity environment, using fecal samples. A subset of samples with abundant extracted DNA (including 3 captive and 3 semi-wild individuals) was selected for whole-genome shotgun sequencing. We found that community diversity did not differ between the semi-wild PH and captive PH, but the semi-wild PH had significantly higher bacterial richness than those in captivity. Relative abundances of all dominant phyla were similar across the semi-wild or captive horses, while those of the non-dominant phyla Tenericutes and Proteobacteria were significantly higher in semi-wild PH than in captive PH. Beta diversity results indicated that bacterial communities of captives and semi-wild horses were clearly separated distinct when considering only composition. Functional profiling of the microbiomes revealed that the semi-wild and captive gut microbiomes were largely similar. However, semi-wild horse microbiomes had higher abundance of bacterial genes related to core metabolic processes, such as carbohydrates, amino acids, and nucleic acid metabolism. The study revealed that semi-wild PH could retain specific non-dominant bacteria and harbor a more diverse microbiome than the captive counterpart, and thus have higher metabolic potential to utilize the complex plants efficiently. These results indicate that change in host lifestyle may play a role in microbiome differentiation in the process of reintroduction, suggesting that a short period of time in captivity is acceptable for PH from the perspective of maintaining the richness of intestinal bacterial flora to some extent.